Mainstreaming environmental education in the teacher education curriculum in the Philippines - Rebecca Rosario Orona Bercasio; Lara Kim Quiopa Remolacio (International Journal of Evaluation and Research in Education (IJERE), 2022)
In the Philippines, environmental education (EE) is a mandate, and at the higher education level, the teacher education programs can serve as a context for EE. During the first semester of the 2016-2017 school year, this pilot study tested teacher education lessons integrated with environmental concepts and principles using EE materials developed by the department of environment and natural resources (DENR) among the 2,420 third year teacher education students in eight institutions of the national network of normal schools (3NS). Data were collected using a validated researcher-made test on environmental concepts and principles. Qualitative data were collected through class observations, focus group conversations, interviews, and authentic student outputs, the capstone projects. The t-test between the pre-test and post-test means (4,838) showed a substantial improvement in the EE test at a level of 0.05 significance across all ten disciplines in eight institutions. The EE mainstreaming in the teacher education curriculum using DENR EE materials and researcher-made and searched EE materials was found effective in enhancing the students' level of competence in terms of environmental concepts and principles. Institutionalization of the mainstreaming of EE in the teacher education curriculum and the cross-cutting inclusion of EE in higher education programs through national policy is strongly recommended.